The Next Frontier - Stem cell and tissue engineering show much promise - New Straits Times, Kasmiah Mustapha (2008)
Since the exploration of stem cell and tissue engineering began years ago, it has created a huge hype in the medical world. Just like any other new findings, scientists all over the world are hoping to come up with a cure for cancer or creating the perfect tissue and organs for humans.